Faecal incontinence in the era of sacral neuromodulation - Sami Hosari; Michaela Ramser; Matthias Turina (Swiss Medical Weekly)
Faecal incontinence is a debilitating condition that significantly affects an individualʼs quality of life. Accurate assessment and a thorough understanding of the underlying aetiology are crucial in determining the appropriate management approach. Conservative management strategies, including dietary modifications, pelvic floor exercises and biofeedback therapy are the first therapeutic steps. If these measures are not effective, patients should be referred to a specialised pelvic floor centre for further treatment evaluations. With the latest updates on national and international guidelines, this review aims to provide a comprehensive overview of current best practices in the management of faecal incontinence, with a particular focus on the role of sacral neuromodulation.